Effects of cutter parameters on shearing stress for lettuce harvesting using a specially developed fixture - Cui, Yongjie; Wang, Wenqi; Wang, Minghui; Ma, Yidong; Fu, Longsheng (International Journal of Agricultural and Biological Engineering, 2021)
To investigate the optimal parameters combination of reciprocating cutter for harvesting hydroponic lettuce automatically, a shear fixture was designed for cutting lettuce stems on a universal materials tester. Effects of blade distance, sliding cutting angle, skew cutting angle, and shearing angle on shearing stress were investigated in this study. The orders of the significance of a single factor and double factors were analyzed using the response surface methodology (RSM). A scanning electron microscope was used to observe the microstructure of the lettuce stem to analyze the shearing characteristics at the microscopic level. The RSM results showed that the order of significance for single factors was (i) sliding cutting angle, (ii) shearing angle, (iii) skew cutting angle, and (iv) blade distance. The sliding cutting angle had a highly significant influence on the shearing stress. The order of significance for double factors was (i) blade distance and shearing angle, (ii) sliding cutting angle and skew cutting angle, and (iii) the sliding cutting angle and shearing angle. A quadratic model of the factors and shearing stress was built according to the response-surface results. The optimized combination of factors that gives the minimum shearing stress was observed that it reduced 69.9% of the maximum shearing stress value. This research can provide a reference for designing lettuce-cutting devices.Keywords: Lactuca sativa, hydroponic lettuce, cutting, optimization, response surface method, micro-structureDOI: 10.25165/j.ijabe.20211404.6346Citation: Cui Y J, Wang W Q, Wang M H, Ma Y D, Fu L S. Effects of cutter parameters on shearing stress for lettuce harvesting using a specially developed fixture. Int J Agric & Biol Eng, 2021; 14(4): 152–158.